Quantum Dot Lasers: High Speed Evanescent Quantum‐Dot Lasers on Si (Laser Photonics Rev. 15(8)/2021). Issue 8 (13th August 2021) - Wan, Yating; Xiang, Chao; Guo, Joel; Koscica, Rosalyn; Kennedy, MJ; Selvidge, Jennifer; Zhang, Zeyu; Chang, Lin; Xie, Weiqiang; Huang, Duanni; Gossard, Arthur C.; Bowers, John E.
Abstract : In article number 2100057, John E. Bowers, Yating Wan, Chao Xiang, and co‐workers report record‐setting quantum dot (QD) distributed feedback lasers on Si with a 3‐dB modulation bandwidth of 13 GHz, a threshold current of 4 mA, a side‐mode‐suppression‐ratio of 60 dB, and a fundamental linewidth of 26 kHz. The broadband QD lasers and the Si‐on‐insulator waveguiding platform can be expanded to build fully functional photonic integrated circuits throughout the O band.